Economic Transformation and Environmental Impact in Central Asia: A Case Study of Kazakhstan’s Shift to Renewable Energy - Smagulova, Assem; Khamzayeva, Assel; Myrzakhmetova, Aida; Yerimpasheva, Aida; Bekmukhametova, Assemgul (International Journal of Energy Economics and Policy, 2025)
This study investigates the economic and environmental impact of Kazakhstan’s transition to renewable energy, focusing on the roles of GDP growth, population dynamics, and technological innovation in shaping CO2 emissions. As global emissions reached a record 36.3 billion tons in 2021, understanding the regional impact of energy decisions is increasingly urgent. Using the STIRPAT model and an autoregressive distributed lag (ARDL) approach, this study analyzes data from 2000 to 2022. Findings, validated through FMOLS and CCR estimators, reveal that energy adoption significantly reduces environmental impact and depicts the importance of supportive policy measures for sustainable economic growth in Central Asia.